2022
DOI: 10.1093/plphys/kiac440
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid-responsive transcription factors PavDof2/6/15 mediate fruit softening in sweet cherry

Abstract: Softening is a key step during fruit ripening that is modulated by the interplay between multiple phytohormones. The antagonistic action of abscisic acid (ABA) and auxin determines the rate of fruit ripening and softening. However, the transcription factors that integrate ABA and auxin signals to regulate fruit softening remain to be determined. In this study, we identified several DNA-binding with One Finger (Dof) transcription factors essential for ABA-promoted fruit softening, based on transcriptome analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 54 publications
(62 reference statements)
1
19
0
Order By: Relevance
“…In tomato ( Solanum lycopersicum ), RNA interference experiment showed the expression of SIDof1 is inhibited during fruit ripening, thus delaying the synthesis of lycopene and the process of fruit ripening ( Wang et al., 2021 ). In cherries, in the presence abscisic acid (ABA), PavDof6 directly binds to the promoter encoding the cell wall modification enzyme gene, while PavDof2/15 plays the opposite role, confirming that some members of the PavDof gene family are involved in early maturation and delayed softening of the fruit ( Zhai et al., 2022 ). Transcriptome analysis of kiwifruit showed that Dof genes play a key role in flower and fruit development ( Brian et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tomato ( Solanum lycopersicum ), RNA interference experiment showed the expression of SIDof1 is inhibited during fruit ripening, thus delaying the synthesis of lycopene and the process of fruit ripening ( Wang et al., 2021 ). In cherries, in the presence abscisic acid (ABA), PavDof6 directly binds to the promoter encoding the cell wall modification enzyme gene, while PavDof2/15 plays the opposite role, confirming that some members of the PavDof gene family are involved in early maturation and delayed softening of the fruit ( Zhai et al., 2022 ). Transcriptome analysis of kiwifruit showed that Dof genes play a key role in flower and fruit development ( Brian et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis , VDof1 and VDof2 regulate vascular cell differentiation throughout the life cycle of a plant by targeting different genes at different developmental stages; VDof proteins negatively regulate vein formation at the seedling stage and target lignin biosynthesis at the reproductive stage ( Ramachandran et al., 2020 ). Previous studies have shown that members of the Dof gene family play a very important role in regulating fruit ripening time and delaying fruit softening in small berries such as cherry( Zhai et al., 2022 ), and kiwifruit ( Brian et al., 2021 ). The fruit of C. humilis is also characterized by hard flesh, and therefore is resistant to storage and transportation, which reduces the impact on fruit quality.…”
Section: Introductionmentioning
confidence: 99%
“…To date, characterization of transcriptional regulators of these softening-related genes is a focused issue in postharvest biology, for the reason that manipulating the expression of distinct upstream regulator using genetic engineering strategy may have potential for prolonging the storage time of the fruit, as is in the case of SlLOB1 in tomato [ 44 ]. Numerous TFs have been identified in fruit softening regulation through targeting the promoters of softening-related genes in various fruits, such as CpERF9 in papaya [ 45 ], SlBES1 in tomato [ 46 ], DkBZR1/2 in kiwifruit [ 47 ], PpERF/ABR1 in peach [ 48 ], FvMYB79 in strawberry [ 49 ], and PavDof2/6/15 in sweet cherry [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trees were planted at a density of 2.5 m 9 1.0 m. In total, 204 surviving F 1 individuals were selected for investigation of fruit firmness at the mature fruit stage from 2016 to 2019. The fruit firmness of two parents ('Rainier' and 'Summit'), three extra-hard-flesh fruit individuals (EH 1, EH 2 and EH 3), three hard-flesh fruit individuals (H 1, H 2 and H 3) and three soft-flesh fruit individuals (S 1, S 2 and S 3) from the F 1 population was assessed at the yellow-white, full red or full colouring (blush type) and dark red or orange-red (blush type) stage from 2016 to 2019 (Garc ıa-G omez et al, 2020(Garc ıa-G omez et al, , 2021Zhai et al, 2022). In addition, 118 sweet cherry accessions were used as a natural segregating population for marker validation (Table S7), which were maintained and grown in the cherry germplasm resource platform of the National Horticultural Germplasm Repository, ZFRI, CAAS, located in Zhengzhou, Henan, China.…”
Section: Plant Materialsmentioning
confidence: 99%